Prognostic Index for Liver Radiation (PILiR) - Laura Callan; Haddis Razeghi; Natalie Grindrod; Stewart Gaede; Eugene Wong; David Tan; Jason Vickress; John Patrick; Michael Lock (Current Oncology)
A Prognostic Index for Liver Radiation (PILiR) for improved patient selection for stereotactic liver-directed radiotherapy (SBRT) was developed. Using a large single-center database, 195 patients treated with SBRT for local control, including 66 with hepatocellular carcinoma (HCC) and 129 with metastatic liver disease, were analyzed. Only patients ineligible for alternative treatments were included. Overall survival was 11.9 months and 9.4 months in the HCC group and metastatic groups, respectively. In the combined dataset, Child–Pugh Score (CPS) (p = 0.002), serum albumin (p = 0.039), and presence of extrahepatic disease (p = 0.012) were significant predictors of early death on multivariable analysis and were included in the PILiR (total score 0 to 5). Median survival was 23.8, 9.1, 4.5, and 2.6 months for patients with 0, 1–2, 3, and 4–5 points, respectively. In the HCC dataset, CPS (p < 0.001) and gross tumor volume (p = 0.013) were predictive of early death. In the metastatic dataset, serum albumin (p < 0.001) and primary disease site (p = 0.003) were predictive of early death. The AUC for the combined, HCC, and metastatic datasets are 0.78, 0.84, and 0.80, respectively. Poor liver function (defined by CPS and serum albumin) and extrahepatic disease were most predictive of early death, providing clinically important expected survival information for patients and caregivers.